SURVAI KESESUAIAN LAHAN UNTUK TANAMAN MANGGIS (Garcinia mangostana L) SEBAGAI TANAMAN KONSERVASI DI KABUPATEN LIMAPULUH KOTA SUMATERA BARAT - Aprisal Aprisal (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2012)
The research was aimed to determine land suitability for manggis (Garcinia mangostana L) as a type of conservative crops in seven regions in District of Lima Puluh Kota. Survey method with purposive random sampling was employed at this study. Soil samples were randomly taken in each region for the physical and chemical analyses in laboratory. Secondary data for climate were obtained at Agriculture Department of the District. Both soil and climate data were arranged and interpreted for manggis growth requirement. The result showed that actual land suitability for each region was classified into S2-S3, with limiting factors were availability of plant nutrients and water, as well as topography. However, by improving soil fertility through OM application as well as soil conservation action, potential land suitability could be increased to be S2-S1 as in Guguk and Bukit Barisan.Keywords: land suitability, soil conservation, manggis